2019
DOI: 10.1111/age.12801
|View full text |Cite
|
Sign up to set email alerts
|

APOB‐associated cholesterol deficiency in Holstein cattle is not a simple recessive disease

Abstract: In 2015, cholesterol deficiency (CD) was reported for the first time as a new recessive defect in Holstein cattle. After GWAS mapping and identification of a disease-associated haplotype, a causative loss-of-function variant in APOB was identified. CD-clinically affected APOB homozygotes showed poor development, intermittent diarrhea and hypocholesterolemia and, consequently, a limited life expectation. Herein, we present a collection of 18 cases clinically diagnosed as CD-affected APOB heterozygotes. CD-clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
3
6
1
Order By: Relevance
“…The high mortality in CD-affected APOB homozygotes can be explained by the lack of ability to absorb and transport dietary lipid components that are a major energy source during the milk-feeding period in calves. Despite significantly lowered concentrations of cholesterol and lipoproteins in APOB heterozygotes, we detected neither limitations nor advantages for intermediary metabolism, health, lactational and reproductive performance, although recent evidence has shown that some APOB heterozygotes might show the clinical CD phenotype (Häfliger et al, 2019). Because of the rather late sampling in early lactation, however, the effects of low circulating cholesterol concentrations on short-term metabolic adaptation to fluctuations in energy balance might not have been detected in the present study.…”
Section: Does the Apob Mutation Cause A Cholesterol Deficiency?contrasting
confidence: 96%
See 1 more Smart Citation
“…The high mortality in CD-affected APOB homozygotes can be explained by the lack of ability to absorb and transport dietary lipid components that are a major energy source during the milk-feeding period in calves. Despite significantly lowered concentrations of cholesterol and lipoproteins in APOB heterozygotes, we detected neither limitations nor advantages for intermediary metabolism, health, lactational and reproductive performance, although recent evidence has shown that some APOB heterozygotes might show the clinical CD phenotype (Häfliger et al, 2019). Because of the rather late sampling in early lactation, however, the effects of low circulating cholesterol concentrations on short-term metabolic adaptation to fluctuations in energy balance might not have been detected in the present study.…”
Section: Does the Apob Mutation Cause A Cholesterol Deficiency?contrasting
confidence: 96%
“…Heterozygous calves, bulls, and nonlactating females are clinically healthy but express distinctly lesser cholesterol and lipoprotein concentrations compared with noncarriers (Gross et al, 2016;Saleem et al, 2016). Recently, a series of APOB heterozygote calves were reported that show the clinical CD phenotype (Häfliger et al, 2019). Therefore, it could be assumed that the CD disorder most likely represents an incomplete dominant inherited metabolic disease with incomplete penetrance in heterozygotes.…”
Section: Introductionmentioning
confidence: 99%
“…The condition occurs due to a mutation in the apolipoprotein B (APoB) gene, which is necessary for lipid metabolism, steroid biosynthesis, and cholesterol absorption from the small intestine (MeNzI et al, 2016). Some heterozygotes calves have reduced blood cholesterol, whereas in recessive homozygotes, blood cholesterol level and triglyceride concentrations are practically zero (KIPP et al, 2016), indicating that Cd represents an incomplete dominant metabolic disease with incomplete penetrance in heterozygotes (HÄFLIgeR et al, 2019). The disease is normally confused with other types of neonatal diarrheas.…”
Section: Resultsmentioning
confidence: 99%
“…In CD carriers, total blood cholesterol appears to be reduced compared with that of noncarriers, indicating that the mechanism of inheritance of CD is partially dominant (Gross et al, 2016;Kipp et al, 2016;Saleem et al, 2016;Gross et al, 2019;Jacinto et al, 2019). Recently, Häfliger et al (2019) determined that some CD carriers become symptomatic as calves, like homozygous CD animals. Cole et al (2016) determined that CD carriers have more favorable genetic merit than noncarrier Holsteins in national evaluations for the traits fat yield, protein yield, SCS, productive life, daughter pregnancy rate, cow conception rate, and heifer conception rate.…”
mentioning
confidence: 99%
“…Carriers of CD could carry less condition as it is known that higher circulating APOB levels are positively correlated with central fat distribution in humans (Okosun et al, 1999). Stunted growth is a symptom of calves with the homozygous APOB mutation and was also observed by Häfliger et al (2019) in clinically affected heterozygotes. However, caution is warranted with these results because of the relatively limited number of cows in our data.…”
mentioning
confidence: 99%